Management of immune checkpoint inhibitor‐related adverse events: A review of case reports - Si, Xiaoyan (Thorac Cancer, 2020)
Immune checkpoint inhibitors represent a major breakthrough in cancer therapy. Immune‐related adverse events (irAEs) may occur during treatment due to their unique mechanism of action. Management of irAEs is based on clinical experience because it is not easy to conduct prospective trials to evaluate the best treatment strategy. Using a combination of search terms in the PubMed and Embase databases, we reviewed all cases in the English language citing toxicities associated with either pembrolizumab, nivolumab, ipilimumab, atezolizumab, tremelimumab, durvalumab, avelumab or any combination of these agents published before 20 May 2019. A total of 128 reports with 239 cases were included in the study. Here, we summarize the spectrum of toxicities, safety in special patients, rechallenging after irAEs and agents used for treatment of irAEs in those reports.